2017
DOI: 10.1007/s11356-017-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions

Abstract: The present study was designed to investigate the residual decline pattern and the risk assessment of 10 different class pesticides, namely azoxystrobin, boscalid, diazinon, diethofencarb, difenoconazole, etofenprox, flubendiamide, paclobutrazol, and pyraclostrobin in young vegetative amaranth (Amaranthus mangostanus) sprayed once or twice under greenhouse growing conditions. Field-incurred samples, collected at 3, 7, or 10 days after application of both treatments, were extracted and purified with the quick, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Indoxacarb’s higher initial residues were attributed to the high amount of active ingredient in the commercial formulation. These findings agree with the results of previous studies that reported that the initial residues of pesticides in crops depend on various factors (formulation, active ingredient, type of crop, dilution factor, and physicochemical properties of pesticides) [ 3 , 17 , 21 ]. In the case of indoxacarb, the log P value was higher than that of cyantraniliprole, which is considered to easily penetrate the crop, leading to higher residues [ 22 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Indoxacarb’s higher initial residues were attributed to the high amount of active ingredient in the commercial formulation. These findings agree with the results of previous studies that reported that the initial residues of pesticides in crops depend on various factors (formulation, active ingredient, type of crop, dilution factor, and physicochemical properties of pesticides) [ 3 , 17 , 21 ]. In the case of indoxacarb, the log P value was higher than that of cyantraniliprole, which is considered to easily penetrate the crop, leading to higher residues [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…If crops do not provide sufficient financial payback, pesticide companies are unwilling to undertake expensive research to register pesticides for them; there will therefore be fewer options for the protection of such crops against pests [ 2 ]. In such cases, growers who cultivate minor crops apply non-registered pesticides to control pests [ 3 ]. The presence of non-registered pesticide residues in crops is of significant concern to consumers due to their health risks [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree with previous studies in the context that the initial residues of pesticides in crops depend on several factors such as the active ingredient (AI), formulation, dilution factor, and type of crop 13 . The AI used in this study was spiromesifen SC 20% and chromafenozide EC 5%, it may be assumed that the higher initial residues of spiromesifen are due to the high concentration of AI present in the formulation products 4 . Pesticide formulation has major effects on its penetration through the leaf surface and dissipation.…”
Section: Resultsmentioning
confidence: 99%
“…Pesticide formulation has major effects on its penetration through the leaf surface and dissipation. Generally, SC formulations retained better than wettable powder (WP) form 4 . The insecticide formulations used in the current study were spiromesifen SC and chromafenozide EC, which are considered to have good adhesion and easy penetration into the crops contributing to high initial residues 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation